3(z-2)+z=4

Simple and best practice solution for 3(z-2)+z=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(z-2)+z=4 equation:


Simplifying
3(z + -2) + z = 4

Reorder the terms:
3(-2 + z) + z = 4
(-2 * 3 + z * 3) + z = 4
(-6 + 3z) + z = 4

Combine like terms: 3z + z = 4z
-6 + 4z = 4

Solving
-6 + 4z = 4

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 4z = 4 + 6

Combine like terms: -6 + 6 = 0
0 + 4z = 4 + 6
4z = 4 + 6

Combine like terms: 4 + 6 = 10
4z = 10

Divide each side by '4'.
z = 2.5

Simplifying
z = 2.5

See similar equations:

| 0.8x+x=27 | | 9x-(2x-3)=45 | | logx+1(4x-15)=2 | | 2x-6=3-x^2 | | 3.4=k-4.3 | | 40=4.25+2.75h | | 5x-120=12 | | (3x+35)=(4x+15) | | 5/x-2=-11/8 | | 2x=1/3-4 | | x^3-x^2+2x=4 | | 1 = y3– 1 | | 5x/3=-13/2 | | y+12=2y-14 | | y+12=2y-24 | | 10+3=8x+3 | | -x-1=239+2x | | (2x/25)-(1/2)=1-(5/2)(x-(1/10)) | | x^3-x^2=500 | | x+10x+3=8x+3 | | -4(x-6)=3(2x-8) | | (-4y+8)(-6)= | | 9/3(6*4/8)=D | | -1-4+8=-x-x+1+6 | | 10x^2y-29xy+10y=0 | | .1(x+40)+.1x=5 | | Y=8x+26 | | 2ex=4 | | Y=27x+-20 | | Y=7x^2+59-36 | | 128x^3y-2xy=0 | | Y=-17x+13 |

Equations solver categories